FARMER DECISION CRITERIA IN DETERMINING AGRICULTURAL PRACTICES DEVELOPMENT OF HORTICULTURE AND ORGANIC FOOD CROPES - Romadhona, Sukron; Puryono, Sri; Mussadun, Mussadun (Socio-Economics/Agribusiness Department, 2024)
Determining national and regional superior commodities is the first step in agricultural development based on the concept of efficiency in order to gain comparative and competitive advantages in facing the globalization of trade so that regional development needs to be carried out in accordance with its development, potential and development policies. The selection or arrangement of priorities is carried out using a logical and structured procedure. The preparation of the strategy is carried out by competent and representative experts related to the alternatives that will be prioritized. AHP analysis is used to solve measurable (quantitative) problems, which require opinion (judgment) or in complex situations. The three strategies used in this research are Providing Production Facilities, Strengthening Human Resources, and Strengthening Farmer Institutions. To find out the Organic Product Development Strategy, a questionnaire was carried out by distributing questionnaires to relevant government officials or agencies totaling around 30 respondents in order to obtain the information that researchers needed. The questionnaires collected from respondents were then tabulated, then analyzed using Expert Choice software. Strategy for Providing Infrastructure and Production Facilities the selection of irrigation networks has the highest percentage, namely 44.8 percent, in the strategy of strengthening human resources, processing training and product marketing, it has the highest percentage, namely 54.9 percent, in the strategy of strengthening institutions, providing market access facilities, it has the highest percentage, namely 71.0 percent, the criteria for strengthening farmers' human resources shows that the alternative strategy that is the main priority in developing organic products is strengthening farmer institutions 46.2 percent.